Research on propagation dynamics of emotional contagion using S3EIR model based on multiple social media platforms - Chen, Hejie; Jin, Jiamin; Sun, Steven; Zhang, Chuyi; Yu, Minshan (Frontiers in Communication, 2025)
IntroductionThe convergence of information technology and the Internet has deeply embedded the media in social life. On different social media platforms, emotion contagion is combined with information dissemination, presenting weak information and strong emotion. In the process of information dissemination, emotion becomes the driving force. This study takes the case of biological parents searching for their abducted son to study the emotional evolution and information dissemination characteristics of hot events in four common social media platforms. Based on the Susceptible-Exposed-Infectious-Recovered (SEIR) model, the exposed is divided into potential positive emotion spreaders, potential negative emotion spreaders, and potential neutral emotion spreaders in this paper. Then, the S3EIR model is constructed based on the path of netizens’ emotional contagion. In order to verify the validity and applicability of the S3EIR model, this paper constructs a dynamical model.MethodsIt uses Python to crawl the comments of the family-seeking event on the four social platforms and uses simulation to simulate and verify the dynamic process of emotional contagion and information dissemination.Results and discussionThe results show that the S3EIR model is feasible and effective in simulating emotional contagion and information flow in social media. The content posted by key opinion leaders on platforms and the emotional atmosphere created in their comment areas significantly impact on the emotional state of netizens. The change in netizens’ emotions is affected by factors such as the characteristics of social media platforms, their user groups, and the functions of the platforms. The model also simulates and verifies the dynamic process of emotion spreading and information diffusion.